Penerapan Keadilan Restoratif Terhadap Tindak Pidana Penganiayaan - Aulia Parasdika; Andi Najemi; Dheny Wahyudhi (Fakultas Hukum, Universitas Jambi, 2022)
The purpose of the study is to find out, analyze, and criticize the implementation and obstacles in the application of restorative justice to the Crime of Persecution (Article 351 Paragraph (1) of the Criminal Code) in terms of Prosecutor's Regulation No. 15 of 2020 at the Jambi District Attorney. Empirical Juridical Research Methods. Conclusion 1) The Jambi District Prosecutor's Office has not been able to handle cases of criminal acts of persecution using Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. 2) Obstacles faced in the application of Restorative Justice by the Jambi District Prosecutor's Office against criminal acts of persecution, including the difficulty of giving directions to the victim to resolve the case at the Prosecutor's Office only, in addition to the desire of the victim to continue the case until the judicial process so that the perpetrator has deterrent effect. Suggestion With this Perja, the practice of resolving criminal acts through restorative justice by prioritizing the restoration of the original state to realize the final result that provides a sense of justice between victims and perpetrators of criminal acts, is expected to be realized in national law in the future. Â ABSTRAK Tujuan penelitian yaitu untuk mengetahui, menganalisis, serta mengkritisi mengenai penerapan serta kendala dalam penerapan keadilan restoratif terhadap Tindak Pidana Penganiayaan (Pasal 351 Ayat (1) KUHP) ditinjau dari Peraturan Kejaksaan Nomor 15 Tahun 2020 Di Kejaksaan Negeri Jambi. Metode Penelitian Yuridis Empiris. Kesimpulan 1) Pihak Kejaksaan Negeri Jambi belum bisa menangani perkara tindak pidana penganiayaan dengan menggunakan Peraturan Kejaksaan Nomor 15 Tahun 2020 tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif. 2) Kendala yang dihadapi dalam Penerapan Keadilan Restoratif oleh Kejaksaan Negeri Jambi terhadap tindak pidana penganiayaan, antara lain susahnya memberikan arahan kepada pihak korban agar menyelesaikan perkara tersebut di tingkat Kejaksaan saja, selain itu adanya keinginan dari korban untuk melanjutkan perkara sampai proses peradilan sehingga pelaku mempunyai efek jera. Saran Dengan adanya Perja ini, praktik penyelesaian tindak pidana melalui restoratif justice dengan mengedepankan pemulihan kembali ada keadaan semula untuk mewujudkan hasil akhir yang memberikan rasa keadilan antara korban dan pelaku tindak pidana, diharapkan dapat terealisasikan dalam hukum nasional pada masa yang akan datang.Â